Effect of early bisoprolol administration on ventricular arrhythmia and cardiac death in patients with non-ST elevation myocardial infarction. Issue 2 (30th November 2015) - Maclean, Edd; Zheng, Sean; Nabeebaccus, Adam; O'Gallagher, Kevin; Stewart, Adrian; Webb, Ian
Abstract : Objective: To investigate the impact of early oral beta blockade in patients presenting with acute non-ST elevation myocardial infarction (NSTEMI). Methods: We retrospectively identified 890 consecutive patients presenting with NSTEMI to a single UK centre from 2012 to 2014. Included patients all received standardised antiplatelet therapy plus low-dose oral bisoprolol (1.25–2.5 mg) within 4 h (mean 2.2±1.36; 'Early Group') or within 5–24 h (mean 15.4±5.7; 'Late Group') of presentation. Patients were followed up for the duration of hospital stay with the incidence of major adverse cardiovascular events (MACE—defined as ventricular arrhythmia, cardiac death or repeat infarction) set as the primary outcome. Multivariate logistic regression models analysed early versus late bisoprolol administration and adjusted for potential confounders. Results: 399 patients were included. Of the patient parameters, only the GRACE score was significantly different between the early (n=99, GRACE 164.5±29.6) and late (n=300, GRACE 156.7±31.4) groups (p=0.033). The early group had significantly fewer ventricular arrhythmias (1 vs 20, p=0.034), cardiac deaths (0 vs 13, p=0.044) and consequently MACE (1 vs 27, p=0.005) than the late group. After adjusting for the confounders of pulse, blood pressure, smoking and creatinine, logistic regression analysis identified early bisoprolol administration as protective for ventricular arrhythmia (p=0.038, OR 0.114, CI 0.015 to 0.885) and MACE (p=0.011, OR 0.064, CI 0.008 to 0.527). There was one episode of symptomatic bradycardia in the late group. Conclusions: This study suggests that low-dose oral bisoprolol administered to patients with NSTEMI within 4 h of admission may be protective and lead to reduced inpatient MACE.